Answer:
(a)
(b)
(c)
Explanation:
Given
Solving (a): Given x = 1; Find PMF(Y)
This implies that, we consider the dataset of the row where x = 1 i.e.
First, calculate P(x=1)
This implies that, we add up the rows where x = 1
So, we have:
The pmf of y is then calculated using:
When x = 1
So, we have:
For i = 0 to 2, we have:
So, the PMF of y given that x = 1 is:
Solving (b): Given x = 2; Find PMF(Y)
This implies that, we consider the dataset of the row where x = 2 i.e.
First, calculate P(x=2)
This implies that, we add up the rows where x = 2
So, we have:
The pmf of y is then calculated using:
When x = 2
So, we have:
For i = 0 to 2, we have:
So, the PMF of y given that x = 2 is:
Solving (c):
This means that, we consider the values of Y for which
is true
These values are 0 and 1
So, we have:
Hence;